Psychometric validation of the English version of the digital wellbeing questionnaire for young adults - Magdalena Liberacka-Dwojak; Germano Vera Cruz; Monika Wiłkość-Dębczyńska; Merve Aktaş Terzioğlu; Andrée-Anne Légaré; Laura Orsolini; Todd Farchione; Tania Lecomte; Sandy Ingram; Riaz Khan; Yasser Khazaal (PLoS ONE, 2026)
Background Digital technologies increasingly impact daily life. Digital wellbeing is emerging as a multidimensional construct encompassing emotional regulation, autonomy, social connection, and respectful online interactions. Objective This study aimed to validate the English version of the 13-item Digital Wellbeing Questionnaire (DWBQ) in young adults. Methods: Data were collected via quota sampling on Prolific, an online crowdsourcing platform. The final sample comprised 1,853 young adults (US n = 933, UK n = 920), including 892 women, 871 men, and 90 non-binary participants., aged 18–25. Confirmatory factor analysis (CFA), measurement invariance testing (across gender and country), reliability analysis, and convergent validity assessments (with the Digital Flourishing Scale and the Digital Stress Scale) were conducted. Results CFA confirmed the four-factor structure (emotional resilience, agency, social connection, and communion), with good model fit (CFI = .969, TLI = .959, RMSEA = .058, SRMR = .038). The DWBQ showed strong internal reliability (α ≥ .80) and measurement invariance across both gender and country. Convergent validity was supported by positive correlations with digital flourishing and negative associations with digital stress. Sociodemographic factors and smartphone use patterns were significantly associated with DWBQ subscales, with gender and relationship status particularly influencing agency and emotional resilience Conclusions The English version of the 13-item DWBQ is a valid and reliable measure of digital wellbeing among young adults in the US and UK. It offers a concise tool for research, educational, and clinical use.